The role of STEAP2 in aggressive prostate cancer traits and androgen responses - LEIA JONES (2021)
The prognosis of localised prostate cancer is generally promising, as many tumours remain dormant and therefore do not require immediate intervention. In contrast, once metastasised, the prognosis for aggressive prostate cancer is often poor, highlighting the need for novel, effective treatment approaches. The expression of the six transmembrane epithelial antigen of the prostate2 (STEAP2) cell surface protein is increased in aggressive prostate cancer compared to normal prostate tissue. In vitro studies have shown STEAP2 to aid in prostate cancer progression, and as such this molecule shows promise as a potential novel therapeutic target in the treatment of advanced disease. The aim of this thesis was to develop a comprehensive understanding of the mechanistic role of STEAP2 in promoting aggressive prostate cancer traits and evaluate if its knock-out has the capacity to reduce the invasive potential of prostate cancer cells in vitro. As prostate cancer is a largely androgen dependent disease, this thesis also aimed to evaluate the effects of STEAP2 inhibition on the expression of the androgen receptor and androgen-regulated genes. This study developed and optimised a protocol for generating a set of 3D prostate cancer spheroids to provide more representative models of the in vivo prostate cancer environment. In this thesis, one commercial anti-STEAP2 polyclonal antibody and a panel of anti-STEAP2 monoclonal antibodies were selected for proof-of-concept studies where their effects on reducing prostate cancer cell viability were assessed. Receptor internalisation of STEAP2 was evaluated upon anti-STEAP2 monoclonal antibody binding to determine its suitability for use with antibody-drug conjugate technology. STEAP2 expression was knocked out using CRISPR/Cas9 genome engineering technology in two prostate cancer cell lines to evaluate its impact on cell proliferation, migration and invasion. Furthermore, gene expression profiling was conducted to explore interactions between STEAP2, the androgen receptor and a panel of androgen-regulated genes (PSA, FKBP5, GPRC6A and TMPRSS2) following: 1) anti-STEAP2 antibody treatment, 2) STEAP2-knockout and 3) the growth of prostate cancer cells in androgen-depleted conditions. The data presented in this thesis demonstrate that inhibition of STEAP2 by both the polyclonal anti-STEAP2 antibody and lead anti-STEAP2 monoclonal antibody significantly reduced prostate cancer cell viability. STEAP2 receptor internalisation was triggered following treatment of prostate cancer cells with the anti-STEAP2 monoclonal antibody, demonstrating its potential utility with antibody-drug conjugate technology in the future. STEAP2 knockout prostate cancer cells exhibited decreased cell proliferation, migration and invasion in comparison to wild-type cells. These promising findings highlight the therapeutic value of STEAP2-knockout in inhibiting invasive tumour cell traits. Gene expression data from both STEAP2-knockout cells and androgen-depleted cells suggest that STEAP2 may be involved in crosstalk between the androgen receptor and androgen-regulated genes. STEAP2 could therefore provide a novel target in conjunction with current conventional androgen deprivation therapy. In conclusion, the in vitro findings presented herein suggest STEAP2 as a viable target for the development of more tailored and personalised therapeutic agents to improve the clinical management of men with aggressive prostate cancer.